PENGELOLAAN ALOKASI DANA DESA (ADD) DALAM MENUNJANG PEMBANGUNAN PEDESAAN : Studi Kasus Desa Nanganesa dan Nesa Manulondo Kecamatan Ndona Kabupaten Ende - Panda, Cerliana; Sayang, Sabulon; Ismail, Nuraini (Program Studi Akuntansi Universitas Flores, 2021)
The purpose of this study is to determine the planning, implementation and accountability process of Village Fund Allocation (ADD) which is based on applicable regulations. The method of analysis used in this research is qualitative descriptive analysis. The data collected in this study are data on the use of Village Fund Allocation in Nanganesa Village and Manulondo Village, Ndona District, Ende Regency from 2012-2015 and data regarding the planning, implementation and accountability process of using the Village Fund Allocation budget in supporting village development. Based on the results of the research, it shows that the planning, implementation and accountability processes are already based on applicable rules. Keywords: Village Fund Allocation, Rural Development